Effect of corn substitution with Enzymated apple pomace on broiler production performance and percentage internal organ of broiler chickens - Djunaidi, Irfan H; Muharlien, Muharlien; Nuningtyas, Yuli Frita (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
Corn is a feedstuff that use as a major component of energy sources and hard to be replaced other feedstuff in poultry ration, even its use is always above 45% in the composition of poultry feed. However, domestic maize availability is limited and the price is changes depend on season harvest time, and most of the availability for animal feed is still imported. Besides that, there is a ban on the use of Antibiotic Growth Promoter (AGP) in poultry feed and drinking water effectively since January 2018, so an effort is needed to replace AGP with natural feed additives or Natural growth promoters (NGP). Based on the above conditions, it is necessary to make efforts to replace corn with local feed ingredients, one of which is apple extraction pomace (apple pomaces). The pomace of apple extraction, if left unchecked, will quickly rot so that it will potentially as an environmental pollutant. The potential of apple pomace extract can be used as a feed ingredient with high sugar and energy content (2300 kcal/kg BK). This research was conducted in the Field Laboratory of Sumber Sekar, Laboratory of Animal Nutrition and Feed, Faculty of Animal Husbandry, Agricultural Technology Laboratory, Brawijaya University. The experiment used 192 DOC broilers and placed them in 8 postal cages per replication. Research on Enzymanted apple pomaces (EAP) as a substitute for corn used a completely randomized design (CRD) P0: basal feed, P1: substitution of EAP 5%, P2: substitution of EAP 10%, P3: substitution of EAP 15%. The variables observed were the production performances include (feed consumption, weight gain, feed conversion ration) and the % internal organs. Based on the research, the results were not significantly different on the production performances and the % of organs in broilers. The use of apple pomaces can be used as a substitute for broiler feed up to a level of 15%.